2021
DOI: 10.3390/ijerph18094694
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Lived Experiences of Adolescents Presenting with Self-Harm and Their Views about Suicide Prevention Strategies: A Qualitative Approach

Abstract: Suicide is a serious global public health problem and the third leading cause of death in those 15–35 years old. Self-harm is the major predictor of future suicide attempts and completed suicide yet remains poorly understood. There is limited evidence on effective interventions for adolescents who present with self-harm. To identify and develop acceptable preventive and therapeutic interventions it is essential to understand the factors that contribute to self-harm and suicide in young people, in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This can be the starting point for a clinical intervention that simultaneously considers both types of behaviors, providing the opportunity to act promptly and comprehensively for the adolescent’s well-being. In this regard, the availability of the Italian version of the RTSHIA will facilitate more accurate assessments of the treatment effects of cultural-tailored interventions or prevention strategies (for the relevance of the cultural differences see, for example, [ 67 ]). The assessment of risk-taking and self-harm behavior is relevant also from a preventive perspective: studying the impact on the severe restrictions due to COVID-19 in Italy, De Luca and colleagues [ 68 ] found that the adolescents considered vulnerable in the pre-pandemic period are at high risk of engaging in SH in the post-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…This can be the starting point for a clinical intervention that simultaneously considers both types of behaviors, providing the opportunity to act promptly and comprehensively for the adolescent’s well-being. In this regard, the availability of the Italian version of the RTSHIA will facilitate more accurate assessments of the treatment effects of cultural-tailored interventions or prevention strategies (for the relevance of the cultural differences see, for example, [ 67 ]). The assessment of risk-taking and self-harm behavior is relevant also from a preventive perspective: studying the impact on the severe restrictions due to COVID-19 in Italy, De Luca and colleagues [ 68 ] found that the adolescents considered vulnerable in the pre-pandemic period are at high risk of engaging in SH in the post-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with NSSI report negative experiences such as misunderstanding, judgment and lack of empathy and credibility when seeking health care (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with NSSI report negative experiences such as misunderstanding, judgment and lack of empathy and credibility when seeking health care 9 - 10 . Health professionals also highlight the lack of formal training, governability and a feeling of unpreparedness to provide health care to adolescents with NSSI 11 .…”
Section: Introductionmentioning
confidence: 99%